Tragic Consequences of Life in Paulo Coelho’s The Spy: Character Analysis - Malinda, Wiwin; Wuntu, Ceisy N.; Mamentu, Agustine C. (Journal of English Culture, Language, Literature and Education, 2024)
The aim of this study is to reveal the tragedy experienced by the main character Mata Hari in Coelho’s The Spy. The main characters struggle to pursue her dream, until the end she had to face the tragedy of her death. This study is using qualitative research. The primary source is the novel itself The Spy. While secondary sources include books related to the analysis of the research and relevant book and resources that support the analysis; quotation, definition, and statement. The death of Mata Hari as the main character in Coelho’s The Spy is a tragedy. That becomes a history of her struggle. Married then moved and lived in Indonesia, precisely in Malang, because Rudolf MacLeod or Mata Hari’s husband was assigned there. With confident that after married will change Mata Hari’s for the better. Yet different things got, Mata Hari was only made a seizure by the husband. The days she lived on the island of Java, only became endless nightmares. The result of this study shows that tragic consequences of life in Mata Hari bring her to death. It because of the way of her life: being divorced, being a popular exotic dancer, becoming a mistress.